The impact of the teaching approach on student performance and perception of first OOP course: case study at FTMSK, Shah Alam / Rosmah Abdul Latif … [et al.] - Abdul Latif, Rosmah; Abdul Ghani, Dalialah; Samsuddin, Noratikah; Mabni, Zulaile (Research Management Institute (RMI), 2006)
Object Oriented Programming (OOP) courses have been taught since 1998 at Universiti Teknologi MARA (UiTM). The syllabus of the first Object-oriented programming course covers basic knowledge in problem solving using objectoriented programming. There are currently two approaches applied to the course: Structured-First-Object-Last(SFOL) and Object-First-Structured-Last(OFSL) approaches. As of now, there is no published study done in Malaysia on the effect of the two different teaching approaches on the students' performance. This study examines student performance: their grades and their problem solving skills. This study involves six groups of students enrolled for the first level of OOP course over a period of three semesters. For each semester, two groups each were taught using the SFOL and the OFSL approaches. At the end of each semester, questionnaires were distributed to all group members to examine the students' ability to solve problems. The data analysed in this study comprise of students' performance, measured through their course work and the final examination results and students problem solving skill using scores obtained from students' answers to problems in the questionnaire. The correlation between students' performance and their problem solving skill is also investigated. Student perceptions towards the course taught also is determined through questionnaire. The correlation between student perception and their performance is also investigated. This study appraises the current teaching method and it is found that students taught using the SFOL approach perform better than those taught using the OFSL approach.